Police Role in Crime Investigation of Fencing Article 480 of the Criminal Code (Study in Polres Demak) - Dwi Fahri Hidayatullah; Gunarto Gunarto; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The purpose of this research identify and analyze the role of the police in criminal investigation of Fencing of Article 480 of the Criminal Code in the jurisdiction of Police Demak and barriers and solutions encountered police officers in criminal investigation of Fencing.The method used is the method of normative and juridical sociologic, the specifications in the study was a descriptive analytical methods of population and sampling are all objects or all of the symptoms or the entire event or the entire unit to be studied, data collection techniques using literature study and interviews, data analysis is qualitative.Result: according to the Criminal Investigation: Examination of the scene, Investigation, Manufacture Minutes, examination of evidence: The search, seizure, Remarks experts, Arrest or Detention and examination of suspects, Resume, file submission. The obstacle is that not everyone knows, does not want to report to law enforcement agencies (police), collusion series of cooperation that is so neat, shrewdness suspect in storing the results of Fencing the Article applied a penalty of less leverage, less personnel in the Resmob Police Demak, because the territory and population is not proportional to the number of personnel Resmob Demak district police, the suspect did not provide information in a clear, witnesses' testimony did not support the investigation, evidence to be filed less, to overcome these obstacles, namely:Key Words: Police; Investigation; Crime; Fencing; Police Demak.